2019
DOI: 10.1002/tox.22771
|View full text |Cite
|
Sign up to set email alerts
|

Dosage‐related beneficial and deleterious effects of ginsenoside Rb1 on mouse oocyte maturation and fertilization and fetal development

Abstract: Ginsenoside Rb1 (GRb1), the major saponin component of ginseng root, has a wide range of therapeutic applications for various diseases. Previously, our group showed that GRb1 triggers ROS‐mediated apoptotic cascades in mouse blastocysts, leading to decreased cell viability and impairment of pre‐ and postimplantation embryonic development, both in vitro and in vivo. In this study, we further found that GRb1 exerted dose‐dependent effects on oocyte maturation and sequent development in vitro. Oocytes preincubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The aim of the study was to investigate the protective effects of GRe on HS-induced damage in porcine oocytes. GRe is critical for the pharmacological activities of ginseng, and similar to other ginsenosides, it has attracted increasing attention for possible use in the treatment of metabolic diseases (Huang et al, 2019). Previous studies have shown that GRe exerts multiple beneficial effects to attenuate cell damage (Sun et al, 2020), reduce the apoptosis rate (Liu et al, 2002) and increase antioxidant activity (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study was to investigate the protective effects of GRe on HS-induced damage in porcine oocytes. GRe is critical for the pharmacological activities of ginseng, and similar to other ginsenosides, it has attracted increasing attention for possible use in the treatment of metabolic diseases (Huang et al, 2019). Previous studies have shown that GRe exerts multiple beneficial effects to attenuate cell damage (Sun et al, 2020), reduce the apoptosis rate (Liu et al, 2002) and increase antioxidant activity (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Yifuning postpones ovarian ageing by suppressing the Rb/p53 signal transduction pathway (Liang et al, 2016). Ginsenoside Rb1 impairs oocyte maturation and embryonic development via involving p53‐, p21‐ and caspase‐3‐dependent regulatory signalling cascades in vitro (Huang et al, 2019). Akt is a serine–threonine protein kinase, which is associated with survival signalling in multiplicity cells, including fibroblasts and neuronal cells, and the inhibiting Akt pathway has been related with apoptosis (Brazil et al, 2004).…”
Section: Possible Biomarkers Of Tcm‐induced Reproductive Toxicitymentioning
confidence: 99%
“…And Rb1 could protect mitochondria from apoptosis 8 . It was also reported that Rb1 has effects on mouse oocyte maturation and has effects on ovarian function in immature rats 9,10 …”
Section: Introductionmentioning
confidence: 96%